Indirectness in Malay Diplomacy (with Particular Reference to Business Dealings and Labour Relations) - Jamaliah Mohd. Ali (Journal of Modern Languages)
This study seeks to explore how indirectness in communication, as practised by the Malays in the business and factory environments, could result in misinterpretation. The study attempts to highlight the adjustment problems faced by both workers and management which must be resolved to ensure harmonious labour management. It also examines briefly the implications with respect to training both workers and managers, especially those from different cultural backgrounds. The paper illustrates the relevance of the study of Indirectness to the resolution of important contemporary issues as well.